LOS GUIONISTAS HABLAN: CÓMO SE CREAN PERSONAJES EN LA FICCIÓN NACIONAL. RESULTADOS DE UN ESTUDIO CUALITATIVO - María Marcos Ramos (Fonseca, Journal of Communication, 2023)
Through a qualitative research based on interviews to Spanish television screenwriters (n=19), this paper studies the creative process of characters depicting immigrants in the main Spanish television shows and films. Thanks to their answers we may understand how these characters are under-represented and stereotyped, as some studies have already pointed out (Igartua; Barrios y Ortega, 2012; Marcos; Igartua; Frutos; Barrios; Ortega y Piñeiro, 2014).